An analysis of multidimensional scaling on educational mapping and human development index in West Sumatra regency - Stefanny Vezalin; Defri Ahmad (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
Welfare is a measuring point for a society to indicate that it is in a prosperous condition. Even though West Sumatra has businesses in various sectors, in terms of equitable distribution of development, it is still uneven. The success of the development and welfare of an area can be known from the human development index (HDI) and education indicators. The purpose of this study was to identify characteristics based on the mapping results of education and HDI in districts and cities in West Sumatra Province using multidimensional scaling analysis. Based on the results of the mapping, what needs to be considered from the level of education and HDI are the Mentawai Islands Regency, Pasaman Regency, Sijunjung Regency, Solok Regency, Solok Selatan Regency, and Dharmasraya Regency with a significance level of 0,01. The value is 99,79%, so the mapping obtained from the multidimensional scaling analysis is acceptable.